2010
DOI: 10.1111/j.1365-2966.2010.17737.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential rotation of main-sequence dwarfs and its dynamo efficiency

Abstract: A new version of a numerical model of stellar differential rotation based on mean‐field hydrodynamics is presented and tested by computing the differential rotation of the Sun. The model is then applied to four individual stars including two moderate and two fast rotators to reproduce their observed differential rotation quite closely. A series of models for rapidly rotating (Prot= 1 d) stars of different masses and compositions are generated. The effective temperature is found convenient to parametrize the di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
85
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 50 publications
(77 reference statements)
15
85
0
Order By: Relevance
“…Kitchatinov & Olemskoy (2011) studied differential rotation along the lower ZAMS for fixed rotation rate and found that the surface shear is a function of the effective temperature alone. Using some artificial models, we find that for the same effective temperature the depth of the convection zone has a significant impact on stellar rotation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kitchatinov & Olemskoy (2011) studied differential rotation along the lower ZAMS for fixed rotation rate and found that the surface shear is a function of the effective temperature alone. Using some artificial models, we find that for the same effective temperature the depth of the convection zone has a significant impact on stellar rotation.…”
Section: Discussionmentioning
confidence: 99%
“…For the G5 V star κ 1 Cet, Walker et al (2007) found P eq = 8.77 days and k = 0.09 +0.006 −0.005 corresponding to δΩ = 0.064 rad/day. Kitchatinov & Olemskoy (2011) computed rotation laws for model stars with 0.8 and 1.0 solar masses for Eri and κ 1 Cet. The results were k = 0.127 for Eri and k = 0.13 for κ 1 Cet.…”
Section: Most Stars: Eri and κ 1 Cetmentioning
confidence: 99%
“…Krause & Rädler 1980) and numerical simulations (e.g. Kitchatinov & Olemskoy 2011;Cole et al 2014) indicate that the magnetic fields of rapidly rotating solar-type stars are only weakly influenced by differential rotation, and they are therefore expected to have very small values of k. Thus, and especially since we simultaneously retrieve both the magnetic field and surface brightness, we did not apply any surface differential rotation in this study.…”
Section: Observed Stars and Their Adopted Stellar Parametersmentioning
confidence: 99%
“…The flow V is specified using the differential rotation model of Kitchatinov & Olemskoy (2011b. A peculiarity of the model is that the eddy transport coefficients are not prescribed but expressed in terms of the entropy gradient, the entropy being one of the dependent variables of the model.…”
Section: Dynamo Modelmentioning
confidence: 99%